Penguatan PENGUATAN USAHA RUMAH TANGGA YANG EFISIEN DAN BERKELANJUTAN DI DESA KECILA KECAMATAN KEMRANJEN KABUPATEN BANYUMAS: PENGUATAN USAHA RUMAH TANGGA YANG EFISIEN DAN BERKELANJUTAN DI DESA KECILA KECAMATAN KEMRANJEN KABUPATEN BANYUMAS - Tjahjani Cahyani (Universitas Wijayakusuma Purwokerto, 2026)
Household businesses in Kecila Village, Kemranjen District, Banyumas Regency, play a vital role in boosting family income and driving local economic growth. However, many business owners still face various challenges, resulting in low productivity and limited competitiveness. Consequently, this community service initiative aims to enhance the capacity of business owners by strengthening operational and financial management, fostering sustainable business practices, and reinforcing sustainable marketing strategies to improve competitiveness. The implementation utilized a Participatory Community Empowerment approach, comprising stages such as needs assessment, outreach, training, mentoring, and monitoring and evaluation. Activities were conducted collaboratively through interactive lectures, discussions, practical bookkeeping exercises, operational management mentoring, and training on digital marketing via social media and online marketplaces. Evaluation was carried out through observation, interviews, and assessments of changes in participants' knowledge and skills following the program. The results indicate an improvement in participants' knowledge and skills regarding simple financial record-keeping, operational cost control, the application of production efficiency principles, and the use of digital media for marketing. Furthermore, participants demonstrated a better understanding of sustainable economic concepts—specifically regarding resource efficiency, waste reduction, and increasing product value-added. This program has positively contributed to enhancing managerial capacity, operational efficiency, and the competitiveness of household businesses, thereby supporting improved community welfare and fostering sustainable village economic development